Síndrome de ojo seco en usuarios que utilizan pantallas electrónicas, atendidos en el centro oftalmológico Vision Care - Sánchez Correa, Paola Viviana (2021)
The advance of Information and Communication Technologies (ICT) during the last decade has motivated the use of new electronic devices worldwide to satisfy work, social and academic requires, and others; which prolonged use predisposes to possible effects on visual health. This research purpose was to determine Dry Eye Syndrome (SOS) by relating a diagnostic test (tear breakup time (TBUT)) with exposure time to electronic screens in users who were attended at "Vision Care" ophthalmologic center. The study was descriptive, prospective, cross-sectional, performed on 60 people (19 men and 41 women); whom tear breakup time was evaluated. Dry Eye Syndrome was considerable in the female gender with a 68% frequency; the age group between 40 and 49 years was the one with the highest prevalence of SOS; and there is a significant negative correlation between TBUT and the hours of exposure to electronic screens (Pearson correlation -0. 70), with the following interpretation: the longer exposure time to a screen, the faster the tear precipitates because of instability or its early evaporation, resulting in a reduced tear breakup time (<10 seconds). Key words: tear breakup, tear film, flicker, hyperosmolarity.